Figure skating: Increasing numbers of revolutions in jumps at the European and World Championships - Rauer, T.; Pape, H.-C.; Knobe, M.; Pohlemann, T.; Ganse, B. (PLOS ONE, 2022)
Figure skating is associated with a high prevalence of sport-specific injuries and overuse symptoms. Impacts are of greater magnitude in jumps with more revolutions that are thus connected to a greater risk of injury. While figure skating programs seem to have recently increased in difficulty, performance trends have not yet been reported in the literature. We hypothesized increasing performance and decreasing age trends of the best athletes who competed at international level in recent years. Furthermore, we aimed to identify and analyse objective performance parameters and to assess a potential link between age and the risk of injury. The development of the number of double, triple and quadruple jumps in the singles figure skating events at the World and European Championships since the introduction of the new ISU Judging System in the 2004/2005 season was analysed using regression statistics and Student`s T-Tests. In all groups, the numbers of jumps with fewer rotations significantly decreased in the favour of jumps with more rotations. Women only started to perform jumps with four rotations in 2019. In the men, the number of quadruple jumps increased from an average of less than one to more than three in recent years (European and World Championships, both p < 0.001). In the European, but not in the World Championships, the average age increased in the men and decreased in the women (European Championships, men and women p = 0.006). Our study was the first to assess performance trends in elite figure skating. The incidence of injuries and overuse syndromes in figure skating needs to be monitored cautiously, as increases can be expected following recent gains in performance and jump complexity.